STUDENTS CAPABILITY IN WRITING DESCRIPTIVE TEXT AT THESECOND YEAR OF SMA NEGERI 1 PURWODADI IN 2010-2011 ACADEMIC YEAR - PRADHIKTA, ADHIB (2011)
This research paper aims at analyzing students capability in writing descriptive text at the second year of SMA Negeri 1 Purwodadi and identifying the problems faced by the students in writing descriptive text. In this research, the writer uses content analysis research. The object of the study is descriptive text at the second year students of SMA N 1 Purwodadi. The data of the research are students worksheet in the form of descriptive text. The data source are taken from informant and document. In collecting data, the writer uses document and interview. The technique for analyzing data are (1) reading the students worksheet in the form of descriptive text, (2) underlining and analyzing the aspects of descriptive text; content, organization, vocabulary, grammar and mechanic, (3) Scoring the students test of writing descriptive text. The result of the analysis shows that students' capability in writing descriptive text can be seen that 29 students who belong to good category (the score 70-84) are 90,62%, 3 students who belong to fair category (the score 55-69) are 9,38%, and there is no student who belongs to very good and poor category. It means that the students' capability in writing descriptive text of the second year level students of SMA Negeri 1 Purwodadi is good. The problems faced by most students in writing descriptive paragraph are grammar. This led too many aspects in writing descriptive paragraph that become problems for students, especially in grammar.